The Role of PAI Teachers in The Implementation of Inclusive Education at SMAN 6 Bandung - Dede Sukandar (Journal of Social Research, 2022)
Background: In the learning process, the presence of a teacher is very important and will not be replaced by a parent. Profession as teacher is a very noble profession because teachers have a very large responsibility to their students. In general, the role of an Islamic teacher is as an educator, advisor, supervisor, leader, motivator, administrator, and evaluator. Objective: This study aims to determine the extent of the role of teachers in implementing inclusive education services at SMAN 6 Bandung. Method: The type of research used in this study is field research. The data collection techniques are observation and interviews. The subjects in this study were PAI teachers, BK teachers, and students with disabilities. Result: The results of this study show that the role of teachers in implementing individual inclusion education has tried their best, but still needs more support from the principal to include all teachers at SMAN 6 Bandung in seminars or workshops about disability services in regular schools. Conclusion: From the presentation above, it shows that in the implementation of inclusive education organized by SMAN 6 Bandung, there is still a lack of participation of teachers in participating in seminars or workshop activities regarding inclusion education, so knowledge about education for students with disabilities has not been thoroughly known by teachers.